2015
DOI: 10.1016/j.tsf.2014.10.079
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence investigation of Cu 2 ZnSnS 4 thin film solar cells

Abstract: Cu 2 ZnSnS 4 (CZTS) is a promising absorber for thin film solar cells which is non-toxic and consists of only abundant elements. In order to achieve higher solar cell efficiencies for this material, a better understanding about its defect structure is necessary. In this paper photoluminescence (PL) from sputtered CZTS thin film solar cells which differ in buffer layer thickness was studied. In the PL spectra three broad peaks could be distinguished between 0.9 and 1.3 eV. The PL measurements as a function of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 33 publications
1
4
0
Order By: Relevance
“…As shown in Fig. 3(c), a large blue shi of peak energy ($25 meV) with slope of 14.3 meV per decade is observed when excitation density is increased, which is consistent with previous observations 21, [25][26][27][28] in solar cell with large potential uctuations. Actually, the large blue shi with the increasing laser power is one feature of donor-acceptor pair (DAP) transition or band to tail (BT) transition.…”
Section: Resultssupporting
confidence: 91%
“…As shown in Fig. 3(c), a large blue shi of peak energy ($25 meV) with slope of 14.3 meV per decade is observed when excitation density is increased, which is consistent with previous observations 21, [25][26][27][28] in solar cell with large potential uctuations. Actually, the large blue shi with the increasing laser power is one feature of donor-acceptor pair (DAP) transition or band to tail (BT) transition.…”
Section: Resultssupporting
confidence: 91%
“…Returning to the question if SnS is really present in the film with x ¼ 0.63, a photoluminescence peak around 1.3 eV [49] due to its band-to-band transition might be observable. However, for this sample it would likely overlap with the band-to-band transition from the CTGS itself.…”
Section: Photoluminescencementioning
confidence: 99%
“…Thus, it should be expected that CZTS exhibits a larger tendency toward disorder, band tails, and band-edge fluctuations. A number of studies have observed such effects (for example, [20], [41], [42]). A comparison of NREL CIGS and Cu 2 ZnSnSe 4 (CZTSe) by constant final state yield spectroscopy indicates that the concentration of near-bandedge states is three to five times higher for CZTSe than for CIGS [46].…”
Section: Cztsmentioning
confidence: 99%